The Effect of Utilizing Powtoon on EFL Junior High School Students’ Vocabulary Achievement - Aryasatya Putra Erdianto; Bambang Arya Wija Putra; Zakiyah Tasnim (Journal on Education, 2024)
In today’s globalized world, having a robust vocabulary is crucial for language proficiency and communication skills, enabling Generation Z students to express themselves fluently and accurately in various contexts (Warschauer & Sykes, 2017). Adequate vocabulary is foundational for proficiency in speaking, reading, writing, and listening. This study investigates the impact of Powtoon on English vocabulary achievement among eighth-grade EFL students in East Java, Indonesia, due to the lack of research in this area. Employing a quasi-experimental design without random assignment, the study involved two classes of eighth-grade EFL students in Jember, Indonesia, during the 2023/2024 academic year. Convenience sampling was used based on proximity to the language lab, class schedule, and teacher recommendations. After four treatment sessions, a post-test showed that the control group’s mean score increased from 76.02 to 78.52, while the experimental group’s score, using Powtoon, rose from 78.33 to 83.70. The N-Gain score percentage increase was 57.52% for the control group and 49.83% for the experimental group. A hypothesis test resulted in a p-value of 0.085, rejecting the null hypothesis and concluding that Powtoon positively impacts students’ English vocabulary achievement.